Rancang Bangun Alat Pendeteksi Alkohol Untuk Makanan Berbais IoT Web Server - Fadhilla Hida Aulia; Bayu Wahyudi; M. Rofi’i (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2025)
Alcohol (ethanol) is often used in food as a mixture to improve flavor or durability, but alcohol consumption can have adverse health effects and trigger psychoactive effects. This research aims to design a tool to detect alcohol content in food using Internet of Things (IoT) technology. This device is designed to be portable, uses MQ-3 gas sensor to detect alcohol content, and is equipped with a Web Server-based data storage system. In addition to alcohol content, this tool is also able to detect the humidity of food samples. The detection results are displayed in real-time through a digital interface, so users can easily access and analyze the data. With this system, it is expected that the public can more easily ensure the safety and halalness of the food consumed. The tool function test obtained the results of the tool working properly, then the tool suitability test using 95% and 70% pure alcohol, obtained results of 90% for 95% alcohol and 72% for 70% alcohol. and finally the suitability test using three food samples, with the results of 40% (food containing alcohol), 6% (food containing hidden alcohol), and 0% (food free of alcohol content).